Spatial-temporal epidemiology of human Salmonella Enteritidis infections with major phage types (PTs 1, 4, 5b, 8, 13, and 13a) in Ontario, Canada, 2008–2009. (December 2015) - Varga, Csaba; Pearl, David; McEwen, Scott; Sargeant, Jan; Pollari, Frank; Guerin, Michele
Abstract Background In Ontario and Canada, the incidence of humanSalmonella enterica serotype Enteritidis (S. Enteritidis) infections have increased steadily during the last decade. Our study evaluated the spatial and temporal epidemiology of the major phage types (PTs ) ofS. Enteritidis infections to aid public health practitioners design effective prevention and control programs. Methods Data onS. Enteritidis infections between January 1, 2008 and December 31, 2009 were obtained from Ontario's disease surveillance system.Salmonella Enteritidis infections with major phage types were classified by their annual health region-level incidence rates (IRs ), monthly IRs, clinical symptoms, and exposure settings. A scan statistic was employed to detect retrospective phage type-specific spatial, temporal, and space-time clusters ofS. Enteritidis infections. Space-time cluster cases' exposure settings were evaluated to identify common exposures. Results 1, 336 cases were available for analysis. The six most frequently reportedS. Enteritidis PTs were 8 (n  = 398), 13a (n  = 218), 13 (n  = 198), 1 (n  = 132), 5b (n  = 83), and 4 (n  = 76). Reported rates ofS. Enteritidis infections with major phage types varied by health region and month. International travel and unknown exposure settings were the most frequently reported settings for PT 5b, 4, and 1 cases, whereas unknown exposure setting, private home, food premise, and international travel were the most frequently reported settings for PT 8, 13, and 13a cases. Diarrhea, abdominal pain, and fever were the most commonly reported clinical symptoms. A number of phage type-specific spatial, temporal, and space-time clusters were identified. Space-time clusters of PTs 1, 4, and 5b occurred mainly during the winter and spring months in the North West, North East, Eastern, Central East, and Central West regions. Space-time clusters of PTs 13 and 13a occurred at different times of the year in the Toronto region. Space-time clusters of PT 8 occurred at different times of the year in the North West and South West regions. Conclusions Phage type-specific differences in exposure settings, and spatial-temporal clustering ofS. Enteritidis infections were demonstrated that might guide public health surveillance of disease outbreaks. Our study methodology could be applied to other foodborne disease surveillance data to detect retrospective high disease rate clusters, which could aid public health authorities in developing effective prevention and control programs.